HER2/neu protein expression and fine needle breast aspiration from Argentinean patients with non-palpable breast lesions - Domínguez, Wendy Gabriela (2010)
The objective of this pilot project was to investigate whether the breast fine needle aspiration (FNA) technique is a useful tool for determining the increased risk of breast cancer in patients with non-palpable breast lesions. FNA is a minimally invasive technique that isolates mammary epithelial cells from breast cells in the suspicious region. In this study, two FNA samples were collected from 12 patients. The level of HER2/neu expression at the mRNA level (in serum) was measured in each patient. As gene amplification is characteristic of cancer cells and may assist in diagnosis and prognostic assessment, it is crucial that gene amplification of HER2/neu in patients with non-palpable breast lesions is compared to breast biopsy results. In serum, the level of HER2/neu was determined by ELISA assay. Gene amplification was determined by PCR and confirmed by IHC employing monoclonal ERRB2 in the FNA sample. The results indicate that FNA has a good correlation with breast biopsy. FNA combined with mammographic imaging is a strong tool for determining favorable treatment options for patients.